Finanças comportamentais: os efeitos de loss aversion e nudges em decisões de investimento em FIIs - Risden Junior, Arlos Eleodoro Seixas (2018)
This research intends to verify the influence that the latent variable Loss Aversion, formed by the union of the constructs Endowment Effect and Status Quo Bias, generates in the perception of decision making on applications in Real Estate Investment Trusts, with the categorical variable Nudges as mediator. FII is an investment modality that has shown, in the brazilian scope, a strong growth in recent years, both in volume and number of investors. With rules that benefit the individual investor, such as the tax exemption on dividends received, this theme is recurring in academia. Aiming at the use of Behavioral Finance, more specifically the Loss Aversion, a concept that represents the fear of losing, overcoming the joy of winning, a structural equations model with partial least squares (PLS-SEM) was conceived with the objective of measuring the influence that this anomaly has on the perception of decision making in investments, specifically in FIIs, with the concept of Nudges as mediator. The definition of Nudges can be represented as a "push" in the right direction, which in this study is symbolized by the information. The research was applied in students of Administration and Accounting of three institutions of higher education of a city of the west of Paraná, being one public and two private. The interviewees were randomly divided into two groups, the same questionnaire was applied to both groups, but only one group received information about the advantages of investment in FIIs. In total there were 145 valid answers, which were tabulated and their values calculated through the conceived model. One feature of the model deserves to be highlighted, all the constructs are formative, which was not found in any other research by the authors After the validation of the PLS-SEM model with formative indicators, the results supported the relationship between the first-order constructs Endowment Effect and Status Quo Bias with the second order latent variable Loss Aversion. The effect found in the model between the latent variables Loss Aversion and Decisions on FIIs, with the categorical variable Nudges as mediator, main objective of this research, was positive and highly significant, being supported by the model. In the group with information the effect on the perception of the decisions about FIIs was more than 0.800 higher than in the group without Nudges. Because it is an exploratory model, the limitation is the impossibility of comparing the results found, besides the sample is formed by young people with an average age under 25 years, which does not form the target public of the investment funds. As a possibility for future research, we highlight the deepening in the studies about the latent variables to identify a greater number of elements that influence the investment decisions, for application in a new model.